Assisted reproductive technology (ART) - Imbar, Tal (Henry Stewart Talks, 2022)
Assisted reproductive technology, Gamete/embryo freezing, Pre-gestational testing, Surrogacy and uterine transplantation, Embryonic stem cells, nuclear transfer and cell therapy